2009
DOI: 10.1038/gt.2009.137
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo functional characterization of gutless recombinant SV40-derived CFTR vectors

Abstract: In cystic fibrosis (CF) respiratory failure caused by progressive airway obstruction and tissue damage is primarily a result of the aberrant inflammatory responses to lung infections with Pseudomonas aeruginosa. Despite considerable improvement in patient survival, conventional therapies are mainly supportive. Recent progress towards gene therapy for CF has been encouraging; however, several factors such as immune response and transduced cell turnover remain as potential limitations to CF gene therapy. As alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…30 , 37 , 38 The wide host range renders it a promising vector not only for the liver but also for organs like the brain and the lung using local administration. 39 , 40 Upon systemic injection, rSV40 mainly targets the hepatocytes, and the dispersion to other tissues can be reduced further by administration into the hepatic artery or portal vein. 41 Although SV40 gives good expression in human cell lines in vivo in mice and rat, the expression levels provided by rSV40 are clearly lower compared to AAV.…”
Section: Discussionmentioning
confidence: 99%
“…30 , 37 , 38 The wide host range renders it a promising vector not only for the liver but also for organs like the brain and the lung using local administration. 39 , 40 Upon systemic injection, rSV40 mainly targets the hepatocytes, and the dispersion to other tissues can be reduced further by administration into the hepatic artery or portal vein. 41 Although SV40 gives good expression in human cell lines in vivo in mice and rat, the expression levels provided by rSV40 are clearly lower compared to AAV.…”
Section: Discussionmentioning
confidence: 99%
“…65 This study also examined CFTR null mice transfected with rSV40/CFTR after Pseudomonas aeruginosa challenge and reported improvements in weight and inflammatory markers such as bronchoalveolar lavage fluid neutrophil counts, interleukin (IL)-1β, and IL-8. Simian vacuolating virus is a circular DNA virus with the ability to integrate into the host cell genome.…”
Section: Additional Viral Vectorsmentioning
confidence: 99%
“…In a recent study, Mueller et al [48] demonstrated that a novel minimal ('gutless') SV40 CFTR expression vector significantly reduced pathology in CFTR knockout mice challenged with Pseudomonas aeruginosa. The authors argue that SV40 is an attractive vector candidate because it offers stable expression through integration and is not immunogenic in rodents.…”
Section: Viral Vectorsmentioning
confidence: 99%